(3Yjhf GdCfHGA aj WHbGJ GdCWHGAs - (3GHf CHj GUjHYI , ehab GdOjf CHh GdYHGS CMeO Hf GdbGSe Hf NdjaI Hf jhfS GdSYOj GdNRQLj,J (B668 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA JQLeI GdTjN GdSOjO GdeJhai HGdbGgQI SfI (B592 (3Hbhdg Gf Chd ef eKdJ Hjf jOjg ef GdNdaGA hCfYe Ydi (B: (3GdBeQ HCMcGe Gddg s
(3BNQgG (B:s
(3ef JQLeI CHj GdaQL GHf Gdba , CKfGA SQO eUfaGJg (B: (3GdeHGMK GdeZQHjI eShOI , hde jJe Je cJGH Yjhf GdCfHGA hWHbGJ GdCWHGA s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B47 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B96s
Keywords: (3GdJGQjNs